Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Terhadap Keaktifan dan Hasil Belajar DSD Negeri Sawojajar 01 - Septiyaningsih, Diyah Nur; Setiyoko, Didik Tri; Yuliyanti, Novi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model on the activeness and learning outcomes of mathematical sentences in third-grade students of Sawojajar 01 Public Elementary School. The type of research used is quasi-experimental, (quasi-experimental) with a Non-equivalent Control Group Design. The study population involved all third-grade students with a total sample of 48 students divided into two classes: the experimental class (N = 23) who received the Teams Games Tournament (TGT) model treatment and the control class (N = 25) who received conventional learning. The data collection instrument consisted of multiple-choice objective tests to measure learning outcomes and closed questionnaires to measure student activeness covering three aspects: task participation, courage to ask/answer, and discussion involvement. Data analysis techniques used descriptive and inferential statistics (t-test) assisted by SPSS. The results of the Shapiro-Wilk normality test showed that the data were normally distributed (Sig. > 0.05) and the Levene homogeneity test showed that the data variance was homogeneous (Sig. > 0.05). The results of the Independent Samples T-Test showed: (1) there was a significant difference in activeness between the experimental and control classes with a Sig. (2-tailed) value of 0.000 < 0.05, and (2) there was a significant difference in learning outcomes with a Sig. (2-tailed) value of 0.005 < 0.05. The average posttest learning outcomes of the experimental class (78.13) were higher than those of the control class (67.12), and the activeness of the experimental class (72.74) was superior to that of the control class (62.64). It was concluded that the Teams Games Tournament (TGT) learning model had a significant effect on the activeness and learning outcomes of elementary school students.